REDEFINISI PERAN GURU DALAM PENDIDIKAN ISLAM: DARI PENGAJAR MENJADI PENDIDIK (MURABBI) - Muhammad Abdurrahman Izzul Islam; Naufal Dwi Ardianto; Ahmad Baikuni; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The development of education in the modern era requires a transformation of teachers' roles, no longer limited to transmitting knowledge but also serving as educators who contribute to students’ character and personality development. In the perspective of Islamic education, this role is embodied in the concept of murabbi, an educator responsible for guiding, nurturing, and developing students’ potential in a holistic manner. This study aims to analyze the redefinition of teachers’ roles in Islamic education from mere instructors to educators (murabbi) and to examine its relevance in addressing contemporary educational challenges. The study employs a library research method with a descriptive qualitative approach through the analysis of relevant literature, including books, scholarly articles, and Islamic education journals. The findings reveal that the concept of murabbi positions teachers as role models who not only transfer knowledge but also instill moral, spiritual, and social values in students. The role of teachers as murabbi has become increasingly significant amidst technological advancements and social changes that may influence the character of younger generations. Therefore, strengthening the role of teachers as murabbi is essential to achieving the objectives of Islamic education, namely producing individuals who are knowledgeable, faithful, and possess noble character.